2012
DOI: 10.1515/hf-2011-0161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systematic variation of wood adherend bending stiffness on fracture properties. Part 2. Revisiting traditional DCB analysis methods

Abstract: Part 1 of the paper evaluated how the orientation and stiffness of the layers in layered beams of constant cross section used in double cantilever beams (DCB) specimens infl uence the stiffness variation of individual adherends along their length. The behavior of bonded DCB specimens made with such materials, of which wood is a common example, are analyzed in this part 2 of the paper to determine errors associated with common data analysis methods for mode I fracture testing: simple beam theory (SBT), correcte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The geometry of this problem is shown, with exaggerated proportions, in Figure 3 a DCB is shown to illustrate a typical adherend. An evaluation of the effect of grain orientation on the values of G c in pure mode I tests is proposed in [126,127], where it is shown that traditional methods for the evaluation of G c , implicitly assuming the stiffness of the beam to be constant, confuse elastic stiffness variability with G c variability, thus generating data with large scatter.…”
Section: Analysis Of Fracture Data Of Bonded Woodmentioning
confidence: 99%
“…The geometry of this problem is shown, with exaggerated proportions, in Figure 3 a DCB is shown to illustrate a typical adherend. An evaluation of the effect of grain orientation on the values of G c in pure mode I tests is proposed in [126,127], where it is shown that traditional methods for the evaluation of G c , implicitly assuming the stiffness of the beam to be constant, confuse elastic stiffness variability with G c variability, thus generating data with large scatter.…”
Section: Analysis Of Fracture Data Of Bonded Woodmentioning
confidence: 99%